Pengabdian Masyarakat Penanaman dan Pemanfaatan Mentimun dan Seledri Sebagai Upaya Pengendalian Penyakit Hipertensi di Dusun Cigadung, Desa Karyamukti, Kota Banjar - Yolanda Priasti Irchamni; Lutfi Hilman Abdullah; Anita Dyah Deswita; Anisa Febriani; Nidya Elpara Dika; Nadia Febriana; Azka Megistriani Putri; Aprilla Andini; Mutiya Rahmah; Yeni Sumartini; Olive Makhira Darlianto; Syahla Farida; Andy Muharry (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Hypertension is a condition where blood pressure is abnormally high with systolic and diastolic numbers showing numbers higher than 140/90 mmHg. As a form of concern for public health, development and training for KWT members, cadres, and hypertension sufferers in RW 03, Cigadung Hamlet, Karyamukti Village were carried out. The community empowerment effort carried out is by planting and processing cucumbers and celery. The method used was participatory-based which involved health education through lectures, questions and answers, as well as filling out pre-test and post-test to measure the increase in knowledge. In addition, joint exercises designed to support a healthy lifestyle were conducted. The result of this community empowerment activity is the difference in knowledge level before and after the intervention with a p-value: 0.000 <0.05.